Combining androgen deprivation and radiation therapy in the treatment of localised prostate cancer: Summary of level 1 evidence and current gaps in knowledge. (November 2022) - Baude, Jérémy; Caubet, Matthieu; Defer, Blanche; Teyssier, Charles Régis; Lagneau, Edouard; Créhange, Gilles; Lescut, Nicolas
Highlights: Localized prostate cancer. Androgen deprivation therapy. Radiation therapy.